Update on Nonsurgical Lung Volume Reduction Procedures - J. Alberto Neder; Denis E. O’Donnell (Canadian Respiratory Journal)
There has been a surge of interest in endoscopic lung volume reduction (ELVR) strategies for advanced COPD. Valve implants, coil implants, biological LVR (BioLVR), bronchial thermal vapour ablation, and airway stents are used to induce lung deflation with the ultimate goal of improving respiratory mechanics and chronic dyspnea. Patients presenting with severe air trapping (e.g., inspiratory capacity/total lung capacity (TLC) < 25%, residual volume > 225% predicted) and thoracic hyperinflation (TLC > 150% predicted) have the greatest potential to derive benefit from ELVR procedures. Pre-LVRS or ELVR assessment should ideally include cardiological evaluation, high resolution CT scan, ventilation and perfusion scintigraphy, full pulmonary function tests, and cardiopulmonary exercise testing. ELVR procedures are currently available in selected Canadian research centers as part of ethically approved clinical trials. If a decision is made to offer an ELVR procedure, one-way valves are the first option in the presence of complete lobar exclusion and no significant collateral ventilation. When the fissure is not complete, when collateral ventilation is evident in heterogeneous emphysema or when emphysema is homogeneous, coil implants or BioLVR (in that order) are the next logical alternatives.